PENGARUH MODEL TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS III SDN PELA - Nurfatihi; Zulkifli; Ratnah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Teams Games Tournament (TGT) learning model on the Indonesian language learning outcomes of third-grade students at SDN Pela. The research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 30 students, with 15 students in the experimental class and 15 in the control class, using pretest and posttest instruments. The results showed that the average posttest score of the experimental class was 82.07, higher than the control class, which scored 69.80. The normality test indicated that the data were normally distributed, the homogeneity test showed homogeneous variance (sig. 0.635 > 0.05), and the t-test revealed a significant difference (sig. 0.001 < 0.05). Therefore, it can be concluded that the implementation of the TGT learning model has a significant effect on improving students’ Indonesian language learning outcomes.